The sum and difference of the areas of Napoleon triangles - Kiss, Sándor (Teaching Mathematics and Computer Science, 2007)
The sum of the areas of the Napoleon triangles is the average of the areas of the three outward equilateral triangles on the sides of triangle ABC, and the differerence of these areas is the area of triangle ABC. In this paper we examine how to change these properties if we build on the sides of the triangle ABC, outwards and inwards, three similar triangles.